2018
DOI: 10.1186/s13017-018-0214-1
|View full text |Cite
|
Sign up to set email alerts
|

LBP rs2232618 polymorphism contributes to risk of sepsis after trauma

Abstract: BackgroundPrevious study revealed that rs2232618 polymorphism (Phe436Leu) within LBP gene is a functional variant and associated with susceptibility of sepsis in traumatic patients. Our aim was to confirm the reported association by enlarging the population sample size and perform a meta-analysis to find additional evidence.MethodsTraumatic patients from Southwest (n = 1296) and Southeast (n = 445) of China were enrolled in our study. After genotyping, the relationship between rs2232618 and the risk of sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Furthermore, Leu436 LBP protein has stronger binding interactions with CD14 (p=0.043) ( 48 ). Lu and their groups confirmed the correlation between genotypic distributions and traumatic sepsis in an enlarged co-located population sample size with 1296 patients in Chongqing (TT vs. TC+CC, p=0.002 for sepsis morbidity rate and p=1.8E-6 for MOD scores, respectively) and 445 patients in Zhejiang (TT vs. TC+CC, p=0.002 for sepsis morbidity rate and p=0.005 for MOD scores, respectively) ( 50 ). Combined analysis of two cohorts also showed relevance between rs2232618 and traumatic sepsis (TT vs. TC+CC, p=4.5×10 -4 for sepsis morbidity rate and p=1.4E-9 for MOD scores, respectively) ( 50 ).…”
Section: Correlation Between Snp In Lbp Gene and Infections Inflammatory Diseases Metabolic Disorders And Cancersmentioning
confidence: 73%
“…Furthermore, Leu436 LBP protein has stronger binding interactions with CD14 (p=0.043) ( 48 ). Lu and their groups confirmed the correlation between genotypic distributions and traumatic sepsis in an enlarged co-located population sample size with 1296 patients in Chongqing (TT vs. TC+CC, p=0.002 for sepsis morbidity rate and p=1.8E-6 for MOD scores, respectively) and 445 patients in Zhejiang (TT vs. TC+CC, p=0.002 for sepsis morbidity rate and p=0.005 for MOD scores, respectively) ( 50 ). Combined analysis of two cohorts also showed relevance between rs2232618 and traumatic sepsis (TT vs. TC+CC, p=4.5×10 -4 for sepsis morbidity rate and p=1.4E-9 for MOD scores, respectively) ( 50 ).…”
Section: Correlation Between Snp In Lbp Gene and Infections Inflammatory Diseases Metabolic Disorders And Cancersmentioning
confidence: 73%
“…Therefore, no conclusive picture regarding risk alleles could be drawn from these data. Interestingly, the F436L SNP examined in this study was associated with a higher prevalence of sepsis in a cohort of trauma victims of Han Chinese origin with a different demographic composition (38,39).…”
Section: Discussionmentioning
confidence: 67%
“…Patients carrying this SNP were excluded from the primary analysis. The SNP further evaluated in this study has been shown by others to be associated with altered sepsis prevalence and mortality in Chinese trauma victims (38,39).…”
Section: Introductionmentioning
confidence: 97%